HAPPY CHINESE NEW YEAR FROM THE VICECHANCELLOR AND THE USM TOP MANAGEMENT - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
Universiti Sains Malaysia ViceChancellor, Professor Dato' Dr. Omar Osman wishes Happy Chinese New Year to the whole USM community, all alumni members, friends and colleagues.